2022
DOI: 10.46586/tches.v2022.i3.141-164
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Parallelepiped Is Back Again: Power Analysis Attacks on Falcon

Abstract: FALCON is a very efficient and compact lattice-based signature finalist of the NIST’s Post-Quantum standardization campaign. This work assesses Falcon’s sidechannel resistance by analyzing two vulnerabilities, namely the pre-image computation and the trapdoor sampling. The first attack is an improvement of Karabulut and Aysu (DAC 2021). It overcomes several difficulties inherent to the structure of the stored key like the Fourier representation and directly recovers the key with a limited number of traces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…When performing all calculations, this difference turns into some small integer factor (in practice, the largest value obtained is (7)) of polynomials at the lowest level of recursion. If the difference occurs in the polynomial z 0 , then, according to formula (11), the situation δ 0 ≠0, δ 1 =0 arises, which is a necessary condition for the operation of formula (12) and the implementation of the attack.…”
Section: Discussion Of Results Of Investigating the Effect Of Floatin...mentioning
confidence: 99%
See 2 more Smart Citations
“…When performing all calculations, this difference turns into some small integer factor (in practice, the largest value obtained is (7)) of polynomials at the lowest level of recursion. If the difference occurs in the polynomial z 0 , then, according to formula (11), the situation δ 0 ≠0, δ 1 =0 arises, which is a necessary condition for the operation of formula (12) and the implementation of the attack.…”
Section: Discussion Of Results Of Investigating the Effect Of Floatin...mentioning
confidence: 99%
“…It has been shown that it is possible to protect against this attack with the help of the correct implementation of calculations. But in [11], a new attack on the implementation was proposed, which made it possible to recover the secret base using power analysis. The conditions for this attack were improved in work [12].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a masked implementation of the Gaussian sampler is provided in [EFG + 22]. Recently, Guerreau et al [GMRR22] proposed a simple power analysis attack on Falcon and a related light countermeasure, and their work was further improved in [ZLYW23], which provides more potential sources of leakage and reduces the number of required traces by new algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…In [KA21], Karabulut and Aysu first performed an EM attack on such computation in Falcon, whose method in their setting can recover the secret key with a few thousand measured traces. Their attack was later improved by Guerreau et al [GMRR22], which reduces the guess space complexity from 2 27 to only 2 11 . However, the protection of the pre-image vector computation in Falcon has so far seldom been discussed.…”
Section: Related Workmentioning
confidence: 99%